Research on active participation of distributed photovoltsics in power grid primary frequency control strategy - Zhang, Runtao; Wang, Lei; Zeng, Siming; Cheng, Ziwei; Su, Can; Li, Zhiwei; Zhang, Hao (Frontiers in Energy Research, 2024)
Distributed photovoltaic systems can actively contribute to the primary frequency regulation of the power grid by reserving capacity. Traditional power reduction methods often employ fixed load reduction ratios, potentially resulting in inadequate frequency regulation capacity and unnecessary reserve power. This paper centers on optimizing power reserve control, starting with the construction of a two-stage model for a photovoltaic grid-connected inverter power generation system. It includes the design of a maximum power estimation method and the implementation of photovoltaic power reduction operation. The article proposes a strategy to utilize photovoltaic backup capacity for achieving primary frequency modulation effects in a short time scale. Additionally, it adopts a variable power reserve ratio operation strategy over the long term, aiming to enhance photovoltaic power generation and optimize solar energy utilization without compromising the grid's frequency and quality. Finally, a MATLAB/Simulink model is developed to validate the effectiveness of the control strategy. Simulation results indicate that the proposed strategy satisfies frequency regulation requirements, enhances power generation efficiency, and improves the economic viability of photovoltaic operations.